(untitled) (Third Sector Social Economic Review, 2021)
As it perceived as a threat to national stability, the initial general approach to the phenomenon of cultural diversity in Western countries was within the framework of assimilationist policies that imposed (state-mandated) the dominant culture and denied cultural differences, but after the increasing opposition to these policies, multiculturalist practices started to emerge in some countries as an approach to recognizing cultural differences. In recent years, there have been some debates on different platforms that multiculturalist practices in Western countries have failed, and so instead of this approach, it is argued that interculturalism, which emphasizes dialogue and interaction between different cultural groups, should be adopted. Especially within the focus on immigrants, this study aims to evaluate the current debates around these two approaches and to make a critical analysis of whether multiculturalism is a failed state policy or not. In accordance with this purpose, it focuses on the problematic analyses in the evaluations made in the relevant scientific literature.